Upending the medical duty to advise: Legislating the standard of care in Singapore. (September 2022) - Amirthalingam, Kumaralingam
The standard of care to which doctors are held in medical practice is based on the peer professional standard in most common law jurisdictions. However, when it comes to the duty to inform the patient of risks in proposed treatment, courts across the common law world have adopted a prudent patient standard to strike a better balance between beneficence and autonomy. Instead of allowing doctors to control the information provided, courts assess what risks are material to a reasonable patient. Singapore is the most recent jurisdiction to follow suit, but the common law development may be short-lived following legislative intervention. This article critically analyses the law on the standard of care in medical negligence, arguing that the legislative reform was based on a misconception of the law. It highlights some of the potential difficulties in implementing the legislative framework.